Case Report: Bionic Reconstruction in an Adult With Obstetric Brachial Plexus Injury - Boesendorfer, Anna; Sturma, Agnes; Gstoettner, Clemens; Pittermann, Anna; Laengle, Gregor; Aszmann, Oskar C. (Frontiers in Rehabilitation Sciences, 2022)
Introduction: Many adults who had a severe Narakas IV obstetric brachial plexus injury (OBPI) suffer from extensive impairments in daily living due to limited hand-arm function. The dramatic loss of axonal support at this very early age of development often render the entire extremity a biologic wasteland and reconstructive methods and therapies often fail to recover any functional hand use. In this scenario bionic reconstruction, including an elective amputation and a subsequent prosthetic fitting, may enable functional improvement in adults suffering from the consequences of such severe brachial plexus injuries. We here describe our experience in treating such patients and lay out the surgical rational and rehabilitation protocol exemplified in one patient. Case Presentation/Methods: A 27-year-old adult with a unilateral OBPI contacted our center. He presented with globally diminished function of the affected upper extremity with minimal hand activity, resulting in an inability to perform various tasks of daily living. No biological reconstructive efforts were available to restore meaningful hand function. An interdisciplinary evaluation, including a psychosocial assessment, was used to assess eligibility for bionic reconstruction. Before the amputation and after the prosthetic fitting functional assessments and self-reported questionnaires were performed. Results: One month after the amputation and de-rotation osteotomy of the humerus the patient was fitted with a myoelectric prosthesis. At the 1.5 year-follow-up assessment, the patient presented with a distinct improvement of function: the ARAT improved from 12 to 20 points, SHAP score improved from 8 to 29, and the DASH value improved from 50 to 11.7. The average wearing times of the prosthesis were 5 to 6 h per day (on 4–5 days a week). Discussion: The options for adults suffering from the consequences of severe OBPIs to improve function are limited. In selected patients in whom the neurological deficit is so severe that biologic hand function is unsatisfactory, an elective amputation and subsequent restoration of the hand with mechatronic means may be an option. The follow-up results indicate that this concept can indeed lead to solid hand function and independence in daily activities after amputation, subsequent prosthetic fitting, and rehabilitation.